Observational Study on Sexual Dimorphism of Carrying Angle among Natives of Ajmer region (Indian Journal of Forensic Medicine & Toxicology, 2020)
Introduction: - The carrying angle is the angle placed between the median axis of arm and median axis offorearm in full extension and supination position. This angle provides the forearms a clear movement withrespect to the hips while walking and is important when carrying objects. Carrying angle is examined invarious pre-placementmedical examination. Carrying angle can be used to differentiate between male and female upper limb. Thiscan be used in partial identification if rich regional data is systemically and statistically collected.Objective:-To collect the statistical data values of carrying angle in both the sexes of Ajmer region.Observing any difference between the caring angle of dominant and non-dominant hand of same individualMethod: - A cross-sectional study was carried out with right handed 100 males and right handed 100females and variations in carrying angle between males and females were calculated using Goniometer. Thevalue is analyzed by mean, standard deviationResults: - In males, mean carrying angle of both upper limbs is 10.720 where as in females mean carryingangle of both upper limbs is found 13.420.Conclusion: The present study showed that the carrying angle was greater in females than in males and it wasgreater in non-dominant arm than in dominant arm.